YOUTUBE WITHIN ESL CLASSROOM: EXPLORING AN INSTRUCTOR’S AND HER LEARNERS’ EXPERIENCES CONCERNING THE AUTHENTICITY OF LANGUAGE AND TECHNOLOGY USE (Malaysian Journal of Learning and Instruction, 2017)
Purpose â€“ This study was aimed to explore the experiences of an instructor and her learners concerning the authenticity of language and technology use in YouTube-aided ESL classroom.Methodology â€“ A qualitative case study was employed involving an ESL instructor and seven learners from a higher learning institution in Malaysia. To achieve the objective, the experiences were uncovered through in-depth interviews and a series of journal entries.Findings â€“ The findings demonstrate that the content of YouTube could be exploited to expose the learners to authentic English. In addition to that, the web 2.0 features of YouTube can familiarise the learners with the current technology application.Significance â€“ This study is significant as it shares with the readers the experiences of an ESL instructor and the learners concerning the potential of YouTube in offering authentic materials and use of technology. By adopting an online video platform and not relying solely on textbook and other printed materials, ESL practitioners are anticipated to be more creative in delivering the subject. This is especially true in teaching todayâ€™s generation who is the digital native. Accordingly, it helps ESL instructors to be able to keep pace with the trendy technology in order to enhance teaching and learning as well as fulfilling current learnersâ€™ technological demand.